Restrukturisasi kognitif untuk mereduksi pikiran negatif pada remaja dengan problem kecemasan sosial - Nurul Izza Pratiwi; Susanti Prasetyaningrum (Procedia : Studi Kasus dan Intervensi Psikologi, 2026)
Social anxiety problem is an excessive fear of social situations, where individuals fear being judged, ridiculed, and excessively afraid of negative evaluations from others. This phenomenon arises from stressful past experiences, such as bullying and family conflict, which can lead to negative thought patterns about oneself and the environment. The aim of this study was to determine whether cognitive restructuring techniques can reduce social anxiety in adolescents. The subjects were 18-year-old adolescents who experienced bullying by peers and teachers during their first year of junior high school. The research methods included interviews, observations, graphic tests (BAUM, DAP, HTP), and the Sack’s Sentence Completion Test (SSCT). The intervention results showed that cognitive restructuring was effective in reducing negative thoughts, such as the belief that everyone will judge them negatively. Subjects became more positive, braver in social interactions, and were able to manage anxiety through more adaptive thinking and adequate social support.